Access to Credit in Rural India: Some Emerging Trends and Patterns - Arora, Sunit (H. : ĐHKT, 2020)
It is found that households falling in upper quintiles of asset ownership borrow more for income generating purposes as compared to borrowing for consumption. Also, these households have a higher share of institutional borrowing in comparison to the households falling in the lower quintile of asset ownership. Even though the share of noninstitutional lending in the rural credit market has declined, the role of professional money lenders has become more important. They now service one-third of the rural credit market in India as compared to 20 percent in 2002-03. As long as the benefits of the schemes to boost rural credit supply accrue disproportionately to the socially and economically better off segments of the rural population, the agrarian crisis which can partly be viewed as a consequence of the inadequacy of credit will only deepen.